Effect of Waiting Time and Process Temperature on the Quality of Commercially Sterilized Flavored Liquid Milk - Nur Fitriana Dewi; Eko Hari Purnomo; Purwiyatno Hariyadi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2019)
In Indonesia, commercially sterilized flavored liquid milk is regulated requiring minimum F0-value of 3.0 minutes. Due to batch thermal processing operation, a waiting time, period for product holding before sterilization process at room temperature, is necessary. Waiting time is identified as a critical factor due to potential increase in initial microbial load. Consequently, increase of waiting time might be associated with the need of higher F0-value. The objective of this study was to evaluate the effect of waiting time (0, 1, 2, 3, 4, 5, and 6 hours) and process temperatures (121.9, 122.6, and 123.9˚C) for fixed processing time (10 minutes) on the selected quality parameters of commercially sterilized flavored liquid milk. Our result showed no significant increase on the number of microbes, pH, and viscosity of the milk after waiting time up to 6 hours. After sterilization, all products tested with waiting time up to 6 hours and processing temperature at 121.9˚C (F0–value of 11.00-13.54 minutes), 122.6˚C (F0–value of 15.49-17.01 minutes), 123.9˚C (F0–value of 20.53-21.46 minutes) were organoleptically acceptable. However, decrease of vitamin B1 (6-7, 9.6-10.4, 22-23%), vitamin C (45-50, 100, and 100%) were observed at processing temperature of 121.9, 122.6, and 123.9˚C, respectively. These findings shows that the use of processing temperature of 121.9˚C (F0-value of 11.00-13.54 minutes) is consider to be the best alternative to produce commercially sterilized flavored liquid milk having waiting time up to 6 hours.